Strategies to improve meat-like properties of meat analogs meeting consumers' expectations. (August 2022) - Chen, Yan Ping; Feng, Xi; Blank, Imre; Liu, Yuan
Abstract: Due to environmental and ethical concerns, meat analogs represent an emerging trend to replace traditional animal meat. However, meat analogs lacking specific sensory properties (flavor, texture, color) would directly affect consumers' acceptance and purchasing behavior. In this review, we discussed the typical sensory characteristics of animal meat products from texture, flavor, color aspects, and sensory perception during oral processing. The related strategies were detailed to improve meat-like sensory properties for meat analogs. However, the upscaling productions of meat analogs still face many challenges (e.g.: sensory stability of plant-based meat, 3D scaffolds in cultured meat, etc.). Producing safe, low cost and sustainable meat analogs would be a hot topic in food science in the next decades. To realize these promising outcomes, reliable robust devices with automatic processing should also be considered. This review aims at providing the latest progress to improve the sensory properties of meat analogs and meet consumers' requirements.